2015
DOI: 10.1118/1.4933196
|View full text |Cite
|
Sign up to set email alerts
|

A continuous surface reconstruction method on point cloud captured from a 3D surface photogrammetry system

Abstract: Purpose: To accurately and efficiently reconstruct a continuous surface from noisy point clouds captured by a surface photogrammetry system (VisionRT). Methods: The authors have developed a level-set based surface reconstruction method on point clouds captured by a surface photogrammetry system (VisionRT). The proposed method reconstructs an implicit and continuous representation of the underlying patient surface by optimizing a regularized fitting energy, offering extra robustness to noise and missing measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Fig. 2 presents the example level set surface reconstructed from one acquired point cloud using the variational method [11]. We used the first 100 surfaces as the training set for manifold learning and training the VAR prediction algorithm.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Fig. 2 presents the example level set surface reconstructed from one acquired point cloud using the variational method [11]. We used the first 100 surfaces as the training set for manifold learning and training the VAR prediction algorithm.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…This missing patch was then “filled in” using the Poisson surface reconstruction process described above, and the reconstructed surface was used for model construction. Previous phantom studies performed by our group have found this technique to have submillimeter accuracy (RMSE) and maximum point errors lower than 2 mm …”
Section: Methodsmentioning
confidence: 93%
“…Previous phantom studies performed by our group have found this technique to have submillimeter accuracy (RMSE) and maximum point errors lower than 2 mm. 33 Figure 2(a) shows the patient setup for the 4DCT + VRT data acquisition. Prior to patient placement on the couch, the VRT system underwent daily calibration.…”
Section: B Empirical Demonstration Using Patient Datamentioning
confidence: 99%
“…Again, it is interesting to see the link between multimodal image fusion-the application this method was intended for in Levin et al [29]-and image-guided therapy, where ICP is still a mainstay when it comes to merging physical coordinate systems such as a stereotactic fixation device or a LINAC to the coordinate system of a volume image [32][33][34][35][36][37][38][39][40][41][42][43]. In the latter case, surface points can either be manually digitized by using a 3D input device [40] or by optical or other non-invasive technologies such as A-mode US [34,35,37,41,42].…”
Section: Surface-and Gradient Based Methodsmentioning
confidence: 99%